The EU's Eastern Neighbourhood Migration, Borders and Regional Stability - Liikanen, Ilkka; Scott, James; Sotkasiira, Tiina (BASEES/Routledge Series on Russian and East European Studies, 2016)
The collapse of the Soviet Union has had profound and long-lasting impacts on the societies of Eastern Europe, the South Caucasus and Central Asia, impacts which are not yet fully worked through: changes in state-society relations, a comprehensive reconfiguration of political, economic and social ties, the resurgence of regional conflicts "frozen" during the Soviet period, and new migration patterns both towards Russia and the European Union. At the same time the EU has emerged as an important player in the region, formulating its European Neighbourhood Policy, and engaging neighbouring states in a process of cross-border regional co-operation. This book explores a wide range of complex and contested questions related to borders, security and migration in the emerging "European Neighbourhood" which includes countries of the Caucasus and Central Asia as well as the countries which immediately border the EU. Issues discussed include new forms of regional and cross-border co-operation, new patterns of migration, and the potential role of the EU as a stabilizing external force.